New insights in the nature of best practice in elite sport system management - exemplified with the organisation of coach education - Böhlke, N. (New Studies in Athletics, 2007)
One of the key results of the existing research into the organisational design of elite sport systems is the identification of a certain convergence in the service portfolios the different systems offer. There is, however, a lack of studies that focus on the actual practices successful systems apply on the operational level; that investigate in how far these practices are related to the success of the systems; that determine if support services and service delivery look similar across different systems; and that evaluate if these practices provide useful lessons from which other systems can learn. Using Swedish athletics and the Norwegian cross-country skiing as examples of particularly successful elite sport systems, this article investigates the open questions with a specific focus on the provision of coach education. It shows that the practices applied in the two systems contradict the best practice in elite sport management received from the existing literature.